PENGARUH TEMPERATUR TERHADAP PERKEMBANGAN NEMATODA SISTA KENTANG (GLOBODERA SPP.) INDONESIA - Lisnawita, Meity S. Sinaga Supramana & Gede Suastika . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2010)
The effect of temperature on the development of Indonesian potato cyst nematode. Potato cyst nematode (PCN) is a serious pathogen of potato and is found in most potato producing areas of the world. In Indonesia, PCN was recently discovered and recognized as major constraint on potato. The growth and behaviour of nematodes are affected by the environment. Therefore, determination of the biology of PCN Indonesian populations is urgently needed to manage this pathogens effectively. The effect of temperature on biology factors of four PCN Indonesian populations (North Java 1, North Java 2, West Java, and Central Java) was studied at different temperatures levels (12, 15, 18, 21 and 24ºC) in the growth chamber. The aim of this research was to study the effect of temperature on development of PCN. Observation was conducted on cyst number, reproduction factor (Rf), survival, fecundity and multiplication of PCN. The optimum temperature range for maximum cysts production with the highest reproduction factor, survival, fecundity and multiplication rate for all populations was 15 - 21ºC. The hatching and development of all PCN populations reduced at temperature below 15ºC or above 21ºC.